MOLECULAR ANALYSIS OF LACTIC ACID BACTERIA ISOLATE SR2 FROM BALI CATTLE RUMEN - I Dewa Made Sukrama; Komang Januartha Putra Pinatih; I Wayan Suardana (Journal of Global Pharma Technology, 2017)
Bali cattle with its distinctively genetic characteristics, namely simple life or easy to adapt on unfavorable environmental condition was known as cattle pioneer. These characteristics were due to specific type of lactic acid bacteria (LAB). These facts indicate that the LAB identification with specific advantages was absolutely necessary for further research in order to prevent incorrect interpretation. Generally, molecular approach is the accurate method of identifying microorganism, and in this case, we used the analysis of the 16S rRNA gene. Research activities began with cultivation of SR2 isolates on specific media deMann Rogosa Sharpe (MRS) followed by Gram stain, catalase test, and formation of CO2 gas. Molecular analysis was performed by PCR of the 16S rRNA gene using primers 27F and 1492R. The PCR products were sequenced and nucleotides data were analyzed by Mega 5.2 Software tool. The results showed that phenotypical isolates of SR2 showed characteristics as LAB isolates, and the results of the 16S rRNA gene analysis showed that isolates SR2 included into Lactococcus lactis strain with a bootstrap value of 100.Keywords - Bali cattle, lactic acid bacteria, molecular analysis, rumen, SR2 isolate